Raw Material Cost Risk Management Strategy to Improve Financial Resilience of Culinary MSMEs in Batu City - Beatrix Liwa Tolok; Cakti Indra Gunawan; R Y Susanto (IRDH International Journal of Social Sciences & Humanities, 2026)
Micro, Small, and Medium Enterprises (MSMEs) in the culinary sector play a crucial role in supporting regional economic development, particularly in Batu City, which is widely recognized as a tourism hub. The high level of tourism activities encourages the growth of culinary MSMEs while simultaneously increasing business competition and operational risks. One of the main challenges faced by culinary MSMEs is the fluctuation in raw material costs, which can directly affect financial stability and business sustainability. Inadequate risk management related to raw material costs may reduce profit margins, disrupt cash flow, and weaken the financial resilience of MSMEs. This study aims to analyze effective raw material cost risk management strategies in enhancing the financial resilience of culinary MSMEs in Batu City. The research method employed is a qualitative approach using a case study design, involving two culinary MSMEs: Ketan KD and Bakso Mantul Balungan Khas Malang. Data were collected through observation, structured interviews with business owners, documentation, and literature study. Data analysis was conducted using SWOT analysis supported by the IFAS, EFAS, and Internal–External (IE) Matrix. The findings indicate that raw material cost risk management strategies, including supplier diversification, planned inventory management, systematic financial recording, and flexible pricing adjustments, are effective in improving cash flow stability, resilience to raw material price fluctuations, and business sustainability. Therefore, appropriate risk management strategies play a crucial role in strengthening the financial resilience of culinary MSMEs in Batu City